Fp-Growth Algorithm For Searching Book Borrowing Transaction Patterns And Study Program Suitability - Lisna Zahrotun; Anna Hendri Soleliza Jones (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
The current development of data has reached a sizeable amount. This is due to the development of the world of information technology which consists of data in it. One technique that can handle abundant data is data mining. Data mining methods are widely used to perform large amounts of data analysis. In the academic field, analysis can be used to determine the patterns of students and lecturers. Whereas in library transactions, analysis can be carried out to determine the patterns of existing book borrowing. This is done to determine the tendency of students with certain study programs to borrow any uku transactions. In this study, the aim of this research is to analyze the patterns of borrowing books from the Ahmad Dahlan University library, which includes borrowing transaction data and the book owner's study program. In addition, in this study, a percentage analysis of the suitability of the book borrower study program and the book owner's study program was also carried out. The stages in this research include data collection, data cleaning, data selection, data transformation, searching for association patterns using the FP-Growth method and pattern evaluation. The test used in this research is the lift ratio. The results of this study are publications in international journals that are in the draft process. Apart from that, the results of this study provide information on the analysis of patterns of lending books in libraries using the FP-Growth method. The resulting pattern is 103 patterns with a support count value of 5 and a confident 10% with the 2 itemset rule, this means that the level of book borrowing is still low. While the results of the analysis of the suitability of books in the study program with the borrower were 31% in accordance with the study program, namely Pharmacy and Public Health Sciences, meaning that there were 69% of students who borrowed books from the library that were not in accordance with their study program.